PUBLIC RELATION DAN PEMBANGUNAN CITRA AGAMIS (Studi Implementasi Manajemen Hubungan Masyarakat Sebagai Upaya Membangun Citra Religius di SMPN 1 Pamekasan) - Mohammad Thoha; Ika Nurul Jannah (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2018)
Education is the most valuable investment to improve the quality of human resources in building a nation. The greatness of a nation is measured by the extent to which its people are educated. Educational institutions and society are two different but inseparable environments that even need each other in their growth and development. The community needs information about what educational institutions are doing. here the role of public relations is absolutely needed. The image of the educational institution depends on the success of the public relations actor. This role was well played by SMPN 1 Pamekasan public relations. Religious values agreed upon as a school culture are communicated to all stakeholders through the implementation of effective community relations management, thus giving birth to a religious image. This article will portray the implementation of public relations management in fostering a religious image in SMPN 1 Pamekasan. With a phenomenological approach, the qualitative data in this article will be described descriptively to be dialogue with previous public relations management theories.